Исследование зависимости саморастекаемости низкоцементного бетонного раствора от типа дефлокулянта - Бражник, Дина Анатольевна; Семченко, Галина Дмитриевна; Бондаренко, А. А.; Самань, А. М.; Повшук, В. В. (НТУ "ХПИ", 2008)
У статті наведено результати саморозтікання низькоцементного бетонного розчину в залежності від типу та кількості дефлокулянтів. Визначено кількісні значення коефіцієнтів саморозтікання мас. Розглянуто причини пластіфікуючої дії дефлокулянтів з точки зору особливостей їх будови та структурування бетону.

The results of low-concrete solution self-flowing depending on the type and content of deflocculants have been presented. The numerical values of self-flowing coefficients of masses have been determined. The reasons of plasticizer effect of deflocculants according to the point of view of their building peculiarities and structure-forming of concrete have been reported.
Keywords: футеровочные бетоны; дефлокулянты; бетонные массы; коэффициент саморастекаемости